Evaluation of social studies curriculum of Iran’s teacher training centers from critical thinking perspective - Naser Noshadi; Mohsen Khademi (فصلنامه نوآوری‌های آموزشی, 2011)
This Study attempts to evaluate social studies curriculum of Iran’s teacher training centers from the critical thinking perspective. Using cluster sampling method, a sample of 313 students and 33 Instructors were selected from among 2020 students and 53 instructors of 4 provinces of Fars, Bushehr, Hormozgan and Isfahan in 2008-2009 academic year. Based on Facione’s model, two scales were used: California Critical Thinking Skill Test (CCTST) containing 5 subscales and California Critical Thinking Disposition Inventory (CCTDI) containing 7 subscales. The reliability of CCTDI and CCTST CCTST were determined using Cronbach’s alpha and Kuder Richardson – 20, respectively. Also, the content of 10 specialty textbooks were analyzed. Findings indicated the weakness of social studies’ students and instructors of Iran’s teacher training centers according to their whole points on dispositions and critical thinking skills and its’ subscales. Also, the differences between frequency of dispositions and critical thinking skill components were investigated.